A Canine Arthroscopic Anterior Cruciate Ligament Reconstruction Model for Study of Synthetic Augmentation of Tendon Allografts - Cook, James L.; Smith, Pat; Stannard, James P.; Pfeiffer, Ferris; Kuroki, Keiichi; Bozynski, Chantelle C.; Cook, Cristi (The Journal of Knee Surgery, 2017)
Novel graft types, fixation methods, and means for augmenting anterior cruciate ligament (ACL) reconstructions require preclinical validation prior to safe and effective clinical application. The objective of this study was to describe and validate a translational canine model for all-inside arthroscopic complete ACL reconstruction using a quadriceps tendon allograft with internal brace (QTIB). With institutional approval, adult research hounds underwent complete transection of the native ACL followed by all-inside ACL reconstruction using the novel QTIB construct with suspensory fixation (n = 10). Contralateral knees were used as nonoperated controls (n = 10). Dogs were assessed over a 6-month period using functional, diagnostic imaging, gross, biomechanical, and histologic outcome measures required for preclinical animal models. Study results suggest that the novel QTIB construct used for complete ACL reconstruction can provide sustained knee stability and function without the development of premature osteoarthritis in a rigorous and valid preclinical model. The unique configuration of the QTIB construct—the combination of a tendon allograft with a synthetic suture tape internal brace—allowed for an effective biologic–synthetic load-sharing ACL construct. It prevented early failure, allowed for direct, four-zone graft-to-bone healing, and functional graft remodeling while avoiding problems noted with use of all-synthetic grafts.
Keywords: anterior cruciate ligament; reconstruction; allograft; arthroscopy; animal model